Ferrostatin-1 post-treatment attenuates acute kidney injury in mice by inhibiting ferritin production and regulating iron uptake-related proteins - Zhao,Yanxiu; Jiang,Binhua; Huang,Dinghui; Lou,Juxiang; Li,Guoshun; Liu,Jianqi; Duan,Fuhui; Yuan,Yuan; Su,Xiaoyan (PeerJ, 2023)
Background Acute kidney injury (AKI) is a common and serious medical condition with high morbidity and mortality. Recent research has highlighted ferroptosis, a novel form of programmed cell death, as a potential therapeutic target in mitigating renal tubular injury in AKI. Ferrostatin-1, a specific ferroptosis inhibitor, has been demonstrated to prevent renal injury through ferroptosis inhibition. Methods Utilizing a murine AKI model, we investigated the effects of Ferrostatin-1 by administering it post-injury. Through high-throughput sequencing and pathological analysis, we focused on the critical role of ferroptosis-related pathways in the treatment. Results Ferrostatin-1 post-conditioning effectively mitigated oxidative damage and reduced iron content associated with AKI. Additionally, critical ferroptosis-related proteins, such as GPX4, SLC7A11, NRF2, and FTH1, exhibited increased expression levels. In vitro, Ferrostatin-1 treatment of HK-2 cells significantly diminished lipid peroxidation and iron accumulation. Furthermore, Ferrostatin-1 was found to downregulate the PI3K signalling pathway. Conclusion Ferrostatin-1 acted as a potential ferroptosis inhibitor with the capacity to enhance antioxidant defences. This study suggests that Ferrostatin-1 could serve as a promising novel strategy for improving the treatment of AKI and promoting recovery from the condition.
Keywords: Iron death; Acute kidney injury; Ferrostatin-1